AUTONOMOUS CONSTITUTIONAL BODIES AND THEIR PLACE IN THE MEXICAN POLITICAL SYSTEM. THE EXPERIENCE OF THE CNDH IN THE RECONFIGURATION OF THE STATE - García Marín, Ignacio (2023)
This research addresses the role played by the Autonomous Constitutional Bodies (OCA) within presidentialism in the Mexican political system. It starts with the analysis of the presidential regime and the Mexican variant, paying special attention to the democratic transition in the 1990s. Subsequently, it analyzes from a constitutional and political point of view, one of the main Mexican constitutional innovations that paved the way for the creation of the OCAs, which facilitated the loss of constitutional powers of the head of state and the end of imperial presidentialism. To facilitate their understanding and legal configuration, the specific case of the National Human Rights Commission (CNDH) is analyzed, which exemplifies well the limits of these institutions, but also their capacity to modernize and democratize the Mexican State. However, this type of institutions would apparently be redesigning the political system in terms of the separation and division of the powers of the State, but without achieving true autonomy and limits for governments with a majority in the chambers